Codifiability and geographical proximity of supply networks in automotive industry - Yeung, Godfrey (ERDKUNDE, 2023)
This methodological paper proposes two codifiability indicators to examine trade and manufacturing statistics and the spatial distribution of value-added manufacturing activities. Codifiability is defined as the level of documentation about the manufacturing processes of a product required to allow tasks to be replicated by other suppliers. First, the codifiability indicators allow researchers to examine products that are grouped under the same sub-product class in conventional statistics, but the manufacture of such products could involve vastly different technologies and thus the level of value-added. A proprietary database was used to delineate the supply networks of automakers in passenger vehicles and their major tier-I suppliers between 2000 and 2015. Second, codifiability allowed the researchers to unpack the spatial distribution of value-addedness of each supplier in the production network, as illustrated by the top two parts suppliers to the automotive industry, Bosch and Denso. The importance of codified standardized commodity parts with lower value-added in the continental European home market illustrates the importance of geographical proximity for Bosch, while the dominance of non-standardized service parts with lower level of codification and higher value-added in its exports to North America is also consistent with the ‘follow the customers’ process in the overseas market reported in the automotive industry. The relative importance of service parts with lower level of codifiability in Denso’s home market illustrates the division of labour with other cross-holding suppliers (especially Aisin and JTEKT) and thus the effects of the interlocking cross-holding of Japanese automobile and parts suppliers, which reconfirms the importance of cultural proximity in Asia’s (Japanese) supply networks.